UPAYA MENURUNKAN BREAKDOWN PADA PERALATAN CHAIN GRATE BOILER DENGAN KOMBINASI METODE FMEA DAN FTAPT. ANGLP - Juniarti, Anita Dyah; Zakaria, Tatan Zakaria; Saefudin, Saefudin Saefudin (Prodi Teknik Industri, Fakultas Teknik, 2025)
Chain Grate Boiler is a vital production engine driver in a factory environment, steam boilers are highly expected for their performance and reliability. Based on history in 2018-2021 boilers in the power plant division experienced an increase in damage or breakdown from the previous year as much as 16 times. Components in chain grate boilers such as chain grate, electric motors, slage conveyors and steam pipelines on the preheater and superheater lines, the main problem of this research is how to reduce the breakdown of Chain Grate Boiler equipment, how to repair and maintain it by analyzing using the FMEA and FTA methods that aims to determine the highest damage value or Risk Priority Number. Based on the results of the analysis, it was found that the highest value of damage to the chain grate boiler equipment was in the chain grate part which produced an RPN value of 486 points which was the highest value of the other equipment analyzed. Furthermore, to find out the root of the problem using the FTA method where four problems were found, namely: understanding of each operator is different, fuel scarcity, purchasing of spare parts indented, and regulation of budget constraints. From these results the researchers got suggestions for improvements using 5W + 1H, namely by evaluating and retraining boiler operators, using different fuels such as household waste, purchasing spare parts with good quality that does not take long and focusing the purchase budget for chain grate boiler equipment.